Análisis y diseño de la arquitectura de procesos para la acreditación - Bazán Infantas, Vanessa (2014)
In the Peruvian University of Applied Science (UPC), the computing and systems school has the necessity to defined, modeled, integrated and optimized the processes that take part in the institutional accreditation, in order to fulfill in a satisfactory way every step to obtain the accreditation in the correct way. This process has the purpose to do the analyses and designs of the architecture of process to the accreditation and facilitate to the Engineering of systems and computing school to identify the essential processes they have to develop and the important aspects for the fulfillment of the institutional accreditation, these processes will be analyzed under the managerial discipline of the methodology of EUP. In addition, we will know what procedures to follow if there are incidents with the institutional accreditation. Since then, the information that generates the developed work will make possible to fulfill the purpose of serving as a structure for the institutional accreditations. So that the work to achieve this purpose will be efficient using the technology as an advantage for the activities of accreditation. Furthermore, in this project we could contemplate the improvement of the virtual company SSIA: teaching coordination management (GDC), management of information of the end of cycle (IFC – DC), management of professional practice (PPP), and reports of control and verification management (SIGERCOV) elaborate for the benefit of the Engineering of systems and computing school. Each of these projects are part of an important work process that involves the institutional accreditation process for the Engineering of systems and computing school, that’s why we will consider them for the analyses and designed of the architecture of processes for the institutional accreditation. In the following document, the project of analyses and design of the architecture of processes for the accreditation is presented (ADAP – AC) that has as main purpose analyzed and designed the architecture of processes for the institutional accreditation for the Engineering of systems and computing school. This architecture of processes will include the most important processes of the institutional accreditation architecture as well as verify that the process could develop in the correct way.